Measuring the Business Cycle Similarity and Convergence Trends in the CEECs Towards the Eurozone with Respect to some Unclear Methodological Aspects - Petr Rozmahel (Austrian Institute of Economic Research (WIFO), 2009)
The adoption of the Euro by Slovakia from January 2009 and the current world economic crises revived a debate on the timing of the adoption of the Euro in the Czech Republic and other CEECs. The purpose of the paper is to contribute to a discussion on the process of joining the Eurozone by the Czech Republic and other candidate countries. The paper provides an analysis of some business cycle similarity and convergence measures using different indicators and detrending techniques. Measures of business cycle similarity are ordinarily used to evaluate preparedness of candidate countries to join the Eurozone. The results indicate continuing convergence of the business cycle similarity between the candidate and Eurozone member countries. The paper also sheds some light on the possible influence of selected detrending techniques on the resulting correlations. It gives a recommendation to interpret the results of business cycle correlation measuring in the close context with used methodology. A short note on a regional approach to analyse the GDP cycles is also included in the text.
Keywords: 330; business cycle; convergence; correlation; eurozone; optimum currency area; Konjunkturzusammenhang; Wirtschaftliche Konvergenz; Eurozone; Optimaler Währungsraum; EU-Mitgliedschaft; EU-Staaten